2018
DOI: 10.1016/j.jacc.2018.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Approach to Selecting Antiplatelet Therapy in Patients With Acute Coronary Syndromes

Abstract: A personalized approach to selecting antiplatelet therapy for patients with ACS may reduce ischemic and bleeding events. (Pharmacogenetics of Clopidogrel in Patients With Acute Coronary Syndromes [PHARMCLO]; NCT03347435).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
147
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 30 publications
6
147
1
2
Order By: Relevance
“…An analysis of the CHARISMA (Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management, and Avoidance) trial showed bleeding events were significantly reduced in clopidogrel‐treated patients who are carriers of CYP2C19 LOF alleles. Additionally, in the prematurely stopped PHARMCLO (Pharmacogenetics of clopidogrel in patients with ACSs) trial ( n = 888), patients with ACS who underwent point‐of‐care genotyping of ABCB1 , CYP2C19*2 , and CYP2C19*17 had a significantly lower incidence of the composite of MI, stroke, and BARC (Bleeding Academic Research Consortium) three to five major bleeding (15.9 vs 25.9% control arm; P < 0.01). Our results demonstrated a lower trend of both ischemic and bleeding endpoints in the genotype‐guided group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An analysis of the CHARISMA (Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management, and Avoidance) trial showed bleeding events were significantly reduced in clopidogrel‐treated patients who are carriers of CYP2C19 LOF alleles. Additionally, in the prematurely stopped PHARMCLO (Pharmacogenetics of clopidogrel in patients with ACSs) trial ( n = 888), patients with ACS who underwent point‐of‐care genotyping of ABCB1 , CYP2C19*2 , and CYP2C19*17 had a significantly lower incidence of the composite of MI, stroke, and BARC (Bleeding Academic Research Consortium) three to five major bleeding (15.9 vs 25.9% control arm; P < 0.01). Our results demonstrated a lower trend of both ischemic and bleeding endpoints in the genotype‐guided group.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y 12 receptor inhibitors are an important part of the management of patients undergoing coronary stenting, especially if they have acute coronary syndromes (ACS). Although ticagrelor and prasugrel are superior in preventing ischemic events, clopidogrel is the most utilized P2Y 12 receptor antagonist worldwide. This is likely due to its lower rate of bleeding and reduced cost.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, personalized antiplatelet therapy with particular consideration of clopidogrel pharmacogenetic and pharmacodynamic characteristics has gained much attention. Unfortunately, large randomized clinical trials (RCTs) that incorporated either platelet function assays or genetic testing have failed to demonstrate any clinical benefit . Furthermore, previous meta‐analyses of such strategies showed conflicting results .…”
Section: Introductionmentioning
confidence: 99%